Revaluación del modelo geológico del campo tello (valle superior del magdalena) y sus implicaciones en el programa de desarrollo (2001)
The Tello field reservoir section was interpreted from 3-D seismic and biostratigraphic analysis from cuttings as an Early Miocene blanket-like fluvial sandstone overlying an Oligocene unconformity. Reservoir stratigraphy was "layer cake". Absence of sandstone in wells was interpreted as a lateral facies change to mudstone. Unexpected results from a recent infill drilling and water injection led to a review of the geological model.  Data from over 800 feet of outcrop, 928 feet of cores from five wells, 21 new biostratigraphic analysis from cores, dipmeter and wireline logs from 35 wells, 5 check-shot and a 36 km2 seismic cube were interpreted and integrated to define a new reservoir model. Sedimentological studies indicate that the reservoir section was deposited in a well oxygenated, current-swept, shallow-marine shelf as agradational tidally influenced cycles, as progradational shorefaces and as tidal bars and channels. High-resolution sequence stratigraphic subdivision of the reservoir allows identification of repeated sections in several wells. Dipmeter data shows low to very high dip angles within the oil-bearing reservoir and confirms the location of low-angle thrust faults, interpreted from well log correlations. The Tello field consists of 5 thrust sheets arranged as a series of partly overlapping ramp anticlines with high-angle dipping backlimbs and low-angle forelimbs. Structural horses involve mostly Monserrate strata. Siliceous siltstones in the Lower Monserrate and Upper Villeta formations act as detachment surfaces for these thrusts. The three easternmost sheets form an antiformal stack that shares the same trailing branch point. Although the roof sequence has been eroded by the Miocene unconformity, the small vertical offset (forelimb against the footwall flat) at the lowest fault-bend indicates that the "Roof sequence" was nearby. By the contrary, the western thrust faults cut the roof sequence as the break-back sequence of deformation occurred. These events are the result of cumulative episodes of deformation and thrust reactivation. Folding of the unconformity and the Miocene strata and the better preservation of the Monserrate strata in the structurally high positions f the field supports reactivation of the westernmost faults. Integration of multiple data sets lead to a reinterpretation of the stratigraphic and structural models that results in better reservoir modeling and planning and recognition of undrilled potential of the Tello field. Estimated new additional oil reserves are about 18 MMBbls. The last 7 wells honored the new reservoir model and daily oil production has increased 80 %.